Physically‐based indicator for identifying ultra‐wideband indoor channel condition. Issue 1 (1st January 2014) - Mucchi, Lorenzo; Sorrentino, Antonio; Carpini, Alessio; Migliaccio, Maurizio; Ferrara, Giuseppe
Abstract : In this study, a model based on the generalised‐K (GK) distribution is proposed for identifying ultra‐wideband (UWB) indoor channel profiles. In particular, an index ( γ ‐index) based on a proper combination of GK parameters is proposed to unambiguously and effectively distinguish among line‐of‐sight (LOS) and non‐LOS propagation conditions. This clear distinction is achieved by defining two non‐overlapping sets which correspond to the two well‐defined profiles. The technique is user‐friendly since it does not call for any complex estimation process. Comparison among the results achieved by both real measurements and IEEE.802.15.4a channel model simulations confirm the soundness of the employed method and the effectiveness of the proposed γ ‐index.